1994
DOI: 10.1177/026765919400900204
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cardiopulmonary bypass on gastric and colonic mucosal perfusion: a tonometric assessment

Abstract: In a study to assess the potential effect of nonpulsatile hypothermic cardiopulmonary bypass (CPB), intramucosal pH (pHi) of the gastric and colonic mucosae was determined by tonometry (n = 8). During the hypothermic phase of CPB, gastric and colonic pHi did not change significantly. Forty minutes after the start of rewarming, despite increases in the cardiac index and mean arterial blood pressure, gastric pHi fell from 7.53 +/- 0.02 to 7.31 +/- 0.03 (p = 0.017) and colonic pHi fell from 7.50 +/- 0.02 to 7.32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
4
10
0
4
Order By: Relevance
“…Gastric microcirculation determined by laser Doppler fluxmetry in our study showed a pathologic response in line with previous studies [5,6]. Interestingly, increased ET-1 and ET A expressions were observed in the CPB group.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gastric microcirculation determined by laser Doppler fluxmetry in our study showed a pathologic response in line with previous studies [5,6]. Interestingly, increased ET-1 and ET A expressions were observed in the CPB group.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have documented alterations in gastric microcirculation during extracorporeal circulation [5,6]. This mechanism provides a plausible explanation for the occurrence of postoperative UGIB.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although these differences in dosage are slight, the measurement and the comparison of gray values determined with densitometry within the vessel and on the area adjacent to the outer vessel wall would not be correct. This increase in perme-ability is also detectable in patients undergoing cardiac operations with CPB [16]. However, the observed perfusion failure of the microcirculation is not predictable from the measured hemodynamic parameters.…”
Section: Discussionmentioning
confidence: 91%
“…Hence, the reduction in splanchnic blood volume is disproportionately greater than that observed in other vascular beds. Therefore, it is not suprising that the reported incidence of gut mucosal hypoperfusion detected by a low intramucosal pH at the end of major surgery is in the range of 24-62% [3], In addition, intramucosal acidosis [41], and increased intes tinal permeability [6] have been demonstrated as a conse quence of gut hypoperfusion after cardiopulmonary by pass operations. Mythen and Webb [5] recently reported increased postoperative complications and costs associat ed with intraoperative mucosal hypoperfusion after car diovascular surgery.…”
mentioning
confidence: 99%